Multistage Adaptive Nanoparticle Overcomes Biological Barriers for Effective Chemotherapy. Issue 31 (30th June 2021) - Wang, Ying; Zhang, Zhanzhan; Zheng, Chunxiong; Zhao, Xinzhi; Zheng, Yadan; Liu, Qi; Liu, Yang; Shi, Linqi
Abstract: Drug delivery systems (DDS) are extensively studied to improve the solubility, stability, pharmacokinetic, and biodistribution of chemotherapeutics. However, the drug delivery efficiency of traditional DDS is often limited by the complicated biological barriers in vivo. Herein, a multistage adaptive nanoparticle (MAN) that simultaneously overcomes multiple biological barriers to achieve tumor‐targeted drug delivery with high efficiency is presented. MAN has a core–shell structure, in which both the core and the shell are made of responsive polymers. This structure allows MAN to present different surface properties to adapt to its surrounding biological microenvironment, thereby achieving enhanced stability in blood circulation, improved tumor accumulation and cellular internalization in tumor tissues, and effective release of drug in cells. With these unique characteristics, the MAN loaded with docetaxel achieves effective tumor suppression with reduced systemic toxicity. Furthermore, MAN can load almost any hydrophobic drugs, providing a general strategy for the tumor‐targeted delivery of hydrophobic drugs to overcome the multiple biological barriers and improve the efficacy of chemotherapy. Abstract : A multistage adaptive nanoparticle (MAN) is developed for efficient chemotherapy. MAN can adapt its surface properties to its surrounding microenvironment, thereby effectively overcoming all major biological barriers during the drug delivery to tumor. MAN can become a feasible delivery strategy to improve the drug availability of hydrophobic drugs to tumor tissues in cancer chemotherapy.